The many faces of pediatric urticaria - Sekerel, Bulent Enis; Ilgun Gurel, Deniz; Sahiner, Umit Murat; Soyer, Ozge; Kocaturk, Emek (Frontiers in Allergy, 2023)
Urticaria is a common disease that can affect individuals of all age groups, with approximately one-quarter of the population experiencing it at least once in their lifetime. Lesions characterized by erythema and itchy hives can appear anywhere on the body. These can vary in size ranging from millimeters to centimeters, and typically clear within 24 h. About 40% of patients with urticaria have accompanying angioedema, which involves localized deep tissue swelling. Urticaria usually occurs spontaneously and is classified into acute and chronic forms, with the latter referring to a condition that lasts for more than 6 weeks. The prevalence of chronic urticaria in the general population ranges from 0.5% to 5%, and it can either be inducible or spontaneous. The most common form of pediatric urticaria is acute and is usually self-limiting. However, a broad differential diagnosis should be considered in children with urticaria, particularly if they also have accompanying systemic complaints. Differential diagnoses of pediatric urticaria include chronic spontaneous urticaria, chronic inducible urticaria, serum sickness-like reaction, urticarial vasculitis, and mast cell disorders. Conditions that can mimic urticaria, including but not limited to cryopyrinopathies, hyper IgD syndrome, Periodic Fever, Aphthous Stomatitis, Pharyngitis and Adenitis (PFAPA), Tumor Necrosis Factor Receptor Associated Periodic Syndrome (TRAPs), and Schnitzler syndrome should also be considered. The many faces of pediatric urticaria can be both easy and confusing. A pragmatic approach relies on clinical foresight and understanding the various forms of urticaria and their potential mimickers. This approach can pave the way for an accurate and optimized diagnostic approach in children with urticaria.